High Performance Architecture and Grid Computing International Conference, HPAGC 2011, Chandigarh, India, July 19-20, 2011. Proceedings - Mantri, Archana; Nandi, Suman; Kumar, Gaurav; Kumar, Sandeep; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereeds proceedings of the International Conference on High Performance Architecture and Grid Computing, HPAGC 2011, held in Chandigarh, India, in July 2011. The 87 revised full papers presented were carefully reviewed and selected from 240 submissions. The papers are organized in topical sections on grid and cloud computing; high performance architecture; information management and network security.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Information storage and retrieval; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Software Engineering; Information Storage and Retrieval; Electronic books